(untitled) (Journal of Human Sciences, 2020)
This research discusses the legal implications upon the perpetrators of incompletely-shared crimes, where a perpetrator does not commit the crime as agreed with the partner, or he/she committed it in addition to another crime that is likely to be committed under the normal course of things by participating in the discussion that took place on the partner’s responsibility for the crime s/he commit with his/her partner. Unlike the crime that a partner planned to contribute in committing it, the legislator decided to hold that partner accountable for the second crime too, because justice requires that he/she does not escape the punishment on the pretext that s/he did not intend to commit the possible outcome of her/his act. But other views of justice argue: the perpetrator is only made accountable for what s/he committed or intended to participate in committing it. This issue necessitated researching to explore differences in determining this responsibility as prescribed in the Libyan and Egyptian laws. The aim is to understand the legislator’s intentions in determining the legal framework of responsibilities in shared crimes and to establish its legal stand in-line with Article (103.ق. ع. ل).